On fractionally integrated logistic smooth transitions in time series - Olanrewaju I. Shittu; OlaOlua S. Yaya (CBN Journal of Applied Statistics, 2011)
Long memory and nonlinearity are two key features of some macroeconomic time series which are characterized by persistent shocks that seem to rise faster during recession than it falls during expansion. A variant of nonlinear time series model together with long memory are used to examine these features in inflation series for three economies. The results which compares favourably with that of van Dijk et al. (2002) elicit some interesting attributes of inflation in the developed and developing economies.
Keywords: C22; C51; C87; 330; Fractional integration; Long memory; Smooth transition autoregression; Inflation rates; Time series